Allergic Diseases Diagnosis and Treatment - Lieberman, Phil; Anderson, John A. (Current Clinical Practice, 2007)
In this updated third edition of the critically-acclaimed volume, expert physicians assemble user-friendly, clinically-oriented guides to aid in the day-to-day management of the allergic patient. With an emphasis on common allergic diseases and the pharmacological tools to control them, Allergic Diseases: Diagnosis and Treatment, Third Edition disseminates the practical knowledge that practitioners have accumulated through practice and teaching in the field of allergy and immunology. This entirely revised third edition updates topics from the second edition and now covers in detail the use of antihistamines and antileukotrienes. Another new chapter will help physicians treat children who experience recurrent respiratory tract infections. Other topics include diagnostic tests, insect stings, sinusitis and otitis media, ocular allergy, atopic dermatitis, and food allergy. Allergic Disease: Diagnosis and Treatment, Third Edition, is intended for the front-line physician who cares for allergic patients and will help any physician improve the care offered to those patients.